2020
DOI: 10.1186/s13063-020-04296-0
|View full text |Cite
|
Sign up to set email alerts
|

Combined extracorporeal shock wave lithotripsy and endoscopic treatment for pain in chronic pancreatitis (SCHOKE trial): study protocol for a randomized, sham-controlled trial

Abstract: Background: Pain is the primary symptom of chronic pancreatitis (CP) and remains a considerable therapeutic challenge. In patients with obstruction of the pancreatic duct, including stones and strictures, endoscopic treatment with or without preceding extracorporeal shock wave lithotripsy (ESWL) has been used for pancreatic duct decompression. The rationale for these procedures is based on the assumption that obstruction of the pancreatic duct leads to ductal hypertension and pain. However, clinical pain sympt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…As a non-invasive physical stimulus, extracorporeal shock wave therapy has been widely used in clinical fields such as osteoarthritis ( 39 ), chronic pancreatitis ( 40 ), and renal calculus ( 41 ). In recent years, it has been found that ECSW can also promote angiogenesis, which not only provides a new idea for the treatment of CHD, but also provides a new choice for adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…As a non-invasive physical stimulus, extracorporeal shock wave therapy has been widely used in clinical fields such as osteoarthritis ( 39 ), chronic pancreatitis ( 40 ), and renal calculus ( 41 ). In recent years, it has been found that ECSW can also promote angiogenesis, which not only provides a new idea for the treatment of CHD, but also provides a new choice for adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The reference population here consisted of 382 (44%) patients who completed the EORTC QLQ‐C30 questionnaire a median of two 1–39 years after their diagnosis. The two groups did not differ in age, sex, alcohol or by aetiology but the reference population had a shorter disease duration ( p < 0.001) and more smoking ( p = 0.029).…”
Section: Resultsmentioning
confidence: 99%
“…There was no difference in pain response among patients needing multiple pancreatic stents compared to patients who had one pancreatic stent, which is reassuring as most patients needed multiple procedures. It should be noted, however, that any intervention will have a major effect on pain, and this is being explored in an ongoing study comparing EP + ESWL with sham interventions 37,38 …”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic duct obstruction is the primary indication for endoscopic and/or surgical therapy in patients with CP according to recent guidelines ( 3 , 14 ). However, the pain-relieving effect of pancreatic duct decompression is debated and currently under evaluation in a sham-controlled trial ( 39 , 40 ). The effect of pancreatic duct decompression on pancreatic functional parameters and morphology is difficult to comprehend because this requires long-term follow-up (for several years), which will hardly be feasible in a sham-controlled study ( 39 ).…”
Section: Discussionmentioning
confidence: 99%